2018
DOI: 10.1111/apt.15043
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virologic response rates in patients with chronic hepatitis C genotype 6 treated with ledipasvir+sofosbuvir or sofosbuvir+velpatasvir

Abstract: Summary Background Hepatitis C virus (HCV) genotype 6 (GT 6) is the predominant genotype among certain Asian populations. The availability of newer DAA options is limited in many parts of Asia. Aim To compare sustained virologic response (SVR‐12) rates between ledipasvir and sofosbuvir (LDV+SOF) and velpatasvir+SOF (SOF+VEL) for patients with HCVGT6 infection. Method Retrospective study of consecutive adult HCVGT6 patients identified via ICD 9 code: 070.5 from United States treatment centers. Treatment was LDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Several well‐designed, robust clinical trials have demonstrated the safety and high curative efficacy of glecaprevir/pibrentasvir and sofosbuvir/velpatasvir among treatment‐naive persons without cirrhosis regardless of HCV genotype. These findings have been confirmed in real‐world cohort studies for both glecaprevir/pibrentasvir and sofosbuvir/velpatasvir . Based on these data, 8 weeks of glecaprevir/pibrentasvir or 12 weeks of sofosbuvir/velpatasvir is recommended for adults eligible for the simplified treatment algorithm.…”
Section: Universal Treatment Of Adults With Chronic Hepatitis C and Smentioning
confidence: 54%
See 2 more Smart Citations
“…Several well‐designed, robust clinical trials have demonstrated the safety and high curative efficacy of glecaprevir/pibrentasvir and sofosbuvir/velpatasvir among treatment‐naive persons without cirrhosis regardless of HCV genotype. These findings have been confirmed in real‐world cohort studies for both glecaprevir/pibrentasvir and sofosbuvir/velpatasvir . Based on these data, 8 weeks of glecaprevir/pibrentasvir or 12 weeks of sofosbuvir/velpatasvir is recommended for adults eligible for the simplified treatment algorithm.…”
Section: Universal Treatment Of Adults With Chronic Hepatitis C and Smentioning
confidence: 54%
“…These findings have been confirmed in real-world cohort studies for both glecaprevir/pibrentasvir (165)(166)(167) and sofosbuvir/velpatasvir. (167)(168)(169)(170)(171) Based on these data, 8 weeks of glecaprevir/pibrentasvir or 12 weeks of sofosbuvir/velpatasvir is recommended for adults eligible for the simplified treatment algorithm.…”
Section: Simplified Hcv Treatment Algorithm For Treatment-naive Adultmentioning
confidence: 99%
See 1 more Smart Citation
“…Because determination of subtypes of GT6 was not performed in this study, our preliminary phylogenetic analysis of 10 patients showed that 6g is the predominant subtype (eight patients) followed by 6a (unpublished data). When comparing the efficacy with other DAA regimens, the treatment result of LDV/SOF in this study was comparable with those from SOF/velpatasvir and glecaprevir/pibrentasvir . A small fraction of patients experienced adverse events in the treatment period, indicating that LDV/SOF treatment is well tolerated and safe.…”
Section: Discussionmentioning
confidence: 51%
“…Most involved fewer than 50 patients. They also presented a wide variation of treatment results, and the SVR rates ranged from 64.1% to 100% . In contrast, this study enrolled patients with a single HCV GT and the most GT6 CHC patients of any study in the literature; it was also conducted in a real‐world setting.…”
Section: Discussionmentioning
confidence: 99%